Capital Budgeting in Multidivision Firms: Information, Agency, and Incentives - Bernardo, Antonio E.; Cai, Hongbin; Luo, Jiang (Review of Financial Studies, 2004)
We examine optimal capital allocation and managerial compensation in a firm with two investment projects (divisions) each run by a risk-neutral manager who can provide (i) (unverifiable) information about project quality and (ii) (unverifiable) access to value-enhancing, but privately costly resources. The optimal managerial compensation contract offers greater performance pay and a lower salary when managers report that their project is higher quality. The firm generally underinvests in capital and managers underutilize resources (relative to first-best). We also derive cross-sectional predictions about the sensitivity of investment in one division to the quality of investment opportunities in the other division, and the relative importance of division-level and firm-level performance-based pay in managerial compensation contracts.